Understanding level of Bay’ salam and Istisna’ among Academy of Contemporary Islamic Studies (ACIS) UiTM Puncak Alam students / Muhammad Zulafnan Zulkikli - Zulkikli, Muhammad Zulafnan (2019)
Bay’ istisna’ and salam were part of contracts of sale in Islam. Both contracts were known as contracts of deferred goods, which the goods delivered after the contract was made. For students of IC110 5C, they had learned both of these contracts during their Semester 1. The problem is to see whether the syllabus provided for the students was compatible with the students to understand or not. The purpose of this research is to measure the understanding level of istisna’ and salam among the students from IC110 5C. This research also aims to determine the most understanding contract between istisna’ and salam. This study used a quantitative method, which is survey questionnaires. The questionnaires were distributed to 33 students from 37 students of IC110 5C. This research used SPSS software. Descriptive and inferential methods are used for data analysing. Both contracts of istisna’ and salam achieved a high score for an understanding level, but salam is the most understand contract among IC110 5C students. This study suggests that future research will need to be more specific in terms of scope, sample, and method of research. The scope needs to be more specific and more suitable for the population that will be conducted, the sample needs to be widened and the method used can be changed for better information.